An Optimal Integer Partition Approach to Coalition Structure Generation - Veera Boonjing; Santit Narabin (My University, 1970)
This paper proposes a new solution to the problem of coalition structure generation using an optimal integer partition. The new partition is the set of set of integers where each integer represents size of a coalition. It includes only elements that no other elements in this partition have values of generated structures higher than them. We show that an element of this partition is a set containing 1 at most one element. Any solutions to the problem of coalition structure generation using the new partition can reduce at least approximately 40% of possible candidate structures when size of coalition members at least 5. Moreover, the bigger the size of coalition members is, the more these solutions outperform the ones using integer partitions.
Keywords: Partition problem; Game Theory and Voting Systems